Micheal Mcconnell

2023-03-14

Find the remainder when the function $f\left(x\right)={x}^{3}-4{x}^{2}+12$ is divided by (x+2).

argueiro6rn

Beginner2023-03-15Added 3 answers

${x}^{3}-4{x}^{2}+12=g\left(x\right)(x+2)+r$

$x=-2$, ${(-2)}^{3}-4{(-2)}^{2}+12=g\left(x\right)((-2)+2)+r$

$-12=0+r$

$r=-12$

$\frac{6}{4}=1$ + remaidr 2

$4\times 1+2=6$

$x=-2$, ${(-2)}^{3}-4{(-2)}^{2}+12=g\left(x\right)((-2)+2)+r$

$-12=0+r$

$r=-12$

$\frac{6}{4}=1$ + remaidr 2

$4\times 1+2=6$

Paxton Houston

Beginner2023-03-16Added 5 answers

$\text{here}\phantom{\rule{1ex}{0ex}}(x-a)=(x-(-2))\Rightarrow a=-2$

$f(-2)={(-2)}^{3}-4{(-2)}^{2}+12=-12$

$f(-2)={(-2)}^{3}-4{(-2)}^{2}+12=-12$